Peningkatan Keterampilan Pemecahan Masalah Matematika, Kolaborasi, dan Kesadaran Sosial Melalui Pembelajaran Think-Pair-Share Pada Siswa Kelas II Sekolah Dasar XYZ Jakarta Barat - Rachellia Citrayani (Syntax Idea)
Problem-solving, collaboration, and social skills are much needed in the 21st century. In the class where the researcher taught, it was found that many students still had difficulty solving mathematical problems independently. In addition, with post-Covid 19 pandemic conditions, students did not appear to have good collaboration skills during group activities in the classroom. Lack of social awareness, which is one of the social skill aspects, could be one of the causes of students’ difficulty in collaborating. This research was a Classroom Action Research that aimed to see the improvement of mathematical problem-solving skills, collaboration, and social awareness through the Think-Pair-Share (TPS) learning method in second-grade students at XYZ Elementary School in West Jakarta. Observation, interview, and student reflection methods were used in data collection, coupled with mathematics tests, to see the development of students’ mathematical problem-solving abilities. There were three research cycles, and at the end of the cycles, it was found that the TPS learning method could improve students’ mathematical problem-solving abilities, collaboration, and social awareness with a moderate level of success.